2019
DOI: 10.1016/j.compchemeng.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

A benders-local branching algorithm for second-generation biodiesel supply chain network design under epistemic uncertainty

Abstract: This paper proposes a possibilistic programming model in order to design a second-generation biodiesel supply chain network under epistemic uncertainty of input data. The developed model minimizes the total costs of the supply chain from supply centers to the biodiesel and glycerin consumer centers. Waste cooking oil and Jatropha plants, as non-edible feedstocks, are considered for biodiesel production. To cope with the epistemic uncertainty of the parameters, a credibility-based possibilistic programming appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…BD algorithm uses the concept of "divide and conquers" to reformulate the original problem into a master problem (MP) and dual subproblem (DSP) in a limited number of iterations. Nowadays, advantages of the BD algorithm, such as a limited number of iterations, less computational time, and guaranteed convergence for largescale problems, make it suitable for many optimization problems (e.g., Pishvaee et al 2010;Shaw et al 2016;Ghezavati et al 2017;Kayvanfar et al 2018;Babazadeh et al 2019;Azadi et al 2019;Mardan et al 2019;Naderi et al 2019;Alkaabneh et al 2020;Gong and Zhang 2021). The primary steps of the BD algorithm work iteratively by outer linearization and relaxation.…”
Section: Model Linearization and Reformulationmentioning
confidence: 99%
“…BD algorithm uses the concept of "divide and conquers" to reformulate the original problem into a master problem (MP) and dual subproblem (DSP) in a limited number of iterations. Nowadays, advantages of the BD algorithm, such as a limited number of iterations, less computational time, and guaranteed convergence for largescale problems, make it suitable for many optimization problems (e.g., Pishvaee et al 2010;Shaw et al 2016;Ghezavati et al 2017;Kayvanfar et al 2018;Babazadeh et al 2019;Azadi et al 2019;Mardan et al 2019;Naderi et al 2019;Alkaabneh et al 2020;Gong and Zhang 2021). The primary steps of the BD algorithm work iteratively by outer linearization and relaxation.…”
Section: Model Linearization and Reformulationmentioning
confidence: 99%
“…The estimated amount of local and foreign demands for biodiesel over the planning horizon is illustrated in Tables and which are taken from Babazadeh et al and Babazadeh et al Iran is a populous country, and more than 75 million liters of gasoline are used daily for its transportation sector according to official statistics. , Therefore, the proposed supply chain is not capable of satisfying such a heavy demand for fuel. In addition, the price of gasoline in Iran is very low compared with European and American countries due to the presence of rich oil resources.…”
Section: Case Studymentioning
confidence: 99%
“…The model was developed to support decision-making in production planning to minimize the cost and cost variations in biodiesel production. In order to build a second-generation biodiesel SC network under epistemic input data ambiguity, Babazadeh et al [49] suggested a potential programming model. The developed model minimized the total SC costs from supply centers to market centers for biodiesel and glycerin.…”
Section: The Robust Optimization In Related Mathematical Models In To Biofuelsmentioning
confidence: 99%